2018
DOI: 10.1016/j.ebiom.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Immune Characteristics of Chinese Diffuse Large B-Cell Lymphoma Patients: Implications for Cancer Immunotherapies

Abstract: Immunotherapeutic agents have demonstrated encouraging signs of clinical utility in non-Hodgkin lymphoma. The goal of this study is to analyze the immune characteristics of Chinese patients with diffuse large B-cell lymphoma (DLBCL) to inform the development of immunotherapies in this patient population. Tumor samples from 211 DLBCL patients were analyzed for cell of origin (COO) and immune characteristics using the NanoString platform as well as MYC protein expression through immunohistochemistry. Lower incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…To our knowledge, it is the first research to analyze the role of OX40/OX40L in early-stage resectable NSCLC and demonstrate its relationships with PD-1/PD-L1, TILs and patients' clinical outcomes. OX40/OX40L has already been studied previously as an immune characteristic biomarker in some other cancer types, including lymphoma, hepatocellular carcinoma, Leukemia, ovarian, neuroblastoma, head and neck squamous cell carcinoma, gastric cancer and breast cancer (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The TILs OX40 was reported to correlate with patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, it is the first research to analyze the role of OX40/OX40L in early-stage resectable NSCLC and demonstrate its relationships with PD-1/PD-L1, TILs and patients' clinical outcomes. OX40/OX40L has already been studied previously as an immune characteristic biomarker in some other cancer types, including lymphoma, hepatocellular carcinoma, Leukemia, ovarian, neuroblastoma, head and neck squamous cell carcinoma, gastric cancer and breast cancer (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The TILs OX40 was reported to correlate with patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…After the exclusion of the main organic and functional causes of adrenal hypertrophy, the most likely possibility is that of stress-related hypertrophy whereby stress resulted in a disturbance of organic homeostasis, due to lymphomatous proliferation. In this regard, we recall the natural immunosuppressive and anti-inflammatory function of corticosteroids produced by the adrenal gland, and the recent scientific evidence of a pro-inflammatory state created by DLBCL [18] . Vincent et al.…”
Section: Discussionmentioning
confidence: 99%
“…already demonstrated in 1994, a statistically significant correlation between adrenal hyperplasia and the presence of neoplasia, both carcinomatous and lymphomatous, suggesting the activation of the HPA axis by hormone-like bioactive factors secreted by lymphomatous / tumor cells as the cause[19]. It has been demonstrated that DLBCL lymphomas may induce the activation of pro-inflammatory genes, creating a pro-inflammatory microenvironment favorable to lymphomatous proliferation [18] . In conclusion, adrenal hyperplasia may be a paraneoplastic condition, and the concept of stress should be evaluated as organic and biochemical changes [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two other cohorts of de novo and relapsed DLBCL patients reported a negative correlation between MYC and PD-L1 [ 63 , 64 ]. Finally, some other studies were not able to detect any correlation between MYC and PD-L1 at all in either DLBCL cell lines [ 80 ], nor in DLBCL patients [ 60 , 66 , 68 , 81 ]. Notably, EBV infection causes B cells to escape from immune surveillance [ 82 , 83 ] partly by PD-L1 overexpression [ 84 , 85 ], adding further complexity to the relationship between MYC and PD-L1 in EBV-associated DLBCL and BL.…”
Section: The Role Of Myc Overexpression On the Immune System In Lymentioning
confidence: 96%
“…The immunoglobulin superfamily member CD80 binds to co-costimulatory molecules from the CD28/B7 family on T cells [ 59 ]. However, in a cohort of 211 de novo DLBCL patients MYC protein overexpression did not correlate with CD40 gene expression, but an association was shown with decreased levels of the co-stimulatory immune checkpoint OX40 ( TNFRSF4 ) gene, decreased T cell receptor signaling molecules and regulatory T cell gene FOXP3 [ 60 ].…”
Section: The Role Of Myc Overexpression On the Immune System In Lymentioning
confidence: 99%